The sacrament of penance in the Orthodox parishes in the North of Russia (since the 18th century till the beginning of the 20th century) - Pulkin Maxim Viktorovich (Institute of Modern Humanitarian Researches, 2019)
The article discusses specific features of the organization of confessional accounting and the implementation of the sacrament of penance in the Russian North. It was revealed that the attitude of the clergy and laity to confession noticeably changed throughout the period under review. Materials of the 18th century paint a picture of the tight control over the implementation of the sacrament. Those who shy away from confession are subjected to various forms of persecution, including fines. Data of the 19th century show that the attitude of church and secular authorities towards confession has undergone major changes. From now on, the basis for the activities of the clergy was preaching, including in the Karelian language, aimed at convincing the local population of the need for annual repentance. Both versions of the impact on the laity did not bring success and were ineffective.